HIV AIDS PREVENTION THROUGH COLLABORATIVE GOVERNANCE AMONG GOVERNMENT, NON GOVERNMENT ORGANIZATION, AND SOCIETY IN DKI JAKARTA PROVINCE - Agung Rheza Fauzi; Amy Yayuk Sri Rahayu (Universitas Respati Indonesia, 2018)
HIV / AIDS cases in Indonesia continue to increase and have spread to all provinces in Indonesia. As the province with the highest number of HIV cases, DKI Jakarta through the Provincial AIDS Commission (KPAP) seeks to prevent the increase of HIV / AIDS cases through collaborative governance between the Government, Non-Governmental Organizations (NGOs), and the public. This collaborative governance is reinforced through Governor Regulation No. 231 of 2015 concerning the Organization and Work Procedure of the Jakarta Capital City Provincial AIDS Commission and the DKI Jakarta Provincial Regulation Number 5 of 2008 concerning HIV and AIDS Prevention. This research was conducted to analyze the process of collaboration between the Government, NGOs and Communities in the DKI Jakarta Province. In addition, this study aimed to provide strategic recommendations for effective collaborative governance in the context of HIV / AIDS prevention in DKI Jakarta Province. This study used descriptive qualitative research methods that described the collaborative process of preventing HIV / AIDS in DKI Jakarta Province. Therefore, this study used a collaborative governance theory that focused on the collaborative process. Based on the research, it was known that collaborative governance has been established between KPAP, Health Office, NGOs, Working Groups (Pokja), and the Community. However, it was still not effective because of the lack of roles of working groups and NGOs that were still dependent on donor agencies in carrying out their activities.